TRANSFORMASI KEBIJAKAN PENDIDIKAN NASIONISIAL DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM: ANALS LANDASAN FILOSOFIS, FORMULASI, DAN IMPLEMENTASI KEBIJAKAN - Faizin, Muhamad; Rika Sa’diyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of national education policy has become a strategic issue in responding to social, technological, economic, and cultural changes in contemporary society. However, policy transformation is often analyzed separately from its philosophical foundations, formulation processes, and implementation dynamics. This study aims to analyze national education policy transformation from the perspective of Islamic Educational Management by examining philosophical foundations, policy formulation processes, implementation practices, and their implications for strengthening Islamic educational institutions. This study employed a qualitative approach using library research methods. Data were collected from books, scientific journals, government regulations, and relevant policy documents and analyzed through descriptive-analytical techniques. The findings indicate that national education policies in Indonesia are philosophically grounded in Pancasila, the 1945 Constitution, and Islamic educational values emphasizing intellectual, moral, and spiritual development. However, policy formulation remains predominantly top-down and has not fully incorporated evidence-based and participatory approaches. Furthermore, policy implementation is influenced by communication, resources, leadership, bureaucratic structures, and organizational culture. The transformation of education policy has encouraged modernization, accountability, and quality improvement in Islamic educational institutions, although challenges related to institutional readiness, resource disparities, and digital divides remain significant. Therefore, a more adaptive, participatory, equitable, and sustainable policy framework is required to strengthen Islamic educational management in Indonesia.